INFLUENCE OF PLANTATION AGE ON PRODUCTION PERFORMANCE OF OIL PALM IN ANDHRA PRADESH - P. MADHAVI LATHA, M. KALPANA; K. MANORAMA (The Journal of Research ANGRAU, 2023)
Oil palm being a perennial plantation crop with high vegetable oil yielding potential is expected to show varied yield potential at different stages of life cycle, with increase in age of the plantation yield increase up to 25 to 30 years. The yield recorded in 5 years old plantation was 93.93 kg of fresh fruit bunch yield (FFB) per palm per year with (13.97 t ha-1) a deviation of 25.53 kg. In 9 years old plantation, the yield recorded was 178.92 kg of fresh fruit bunch yield (FFB) per palm per year (26.33 t ha-1) with a yield deviation of 50.62 kg, it was 48 percent more yield than that of 5 years old palms and 16 percent less than to 24 years old palms. In 24 years old palms the average yield recorded was 215.35 kg of fresh fruit bunch yield (FFB) per palm per year (31.80 t ha-1) with a deviation of 70.38 kg. Among 18 palms studied in each of three age groups, 66.66 per cent of palms recorded 50 to 100 kg of FFB per palm per year at 5 years age of plantation. In 9 year old palms 66.66 percent of palms recorded 150 to 250 kg of FFB per palm per year where as in 24 years old palms, 33.33 percent of palms recorded 200 to 250 kg of FFB per palm per year and 33.33 percent of palms recorded more than 250 kg. Regarding per hectare yield in 5 years old plantation 50 percent of palms recorded 10 to 15 t ha-1 of FFB, while in 9 years old plantation 78 percent of palms recorded more than 20 t ha-1 and in 24 years old plantation 66 percent of palms recorded more than 30 t ha-1 of FFB yield per year. This data reflects that up to 24 years, oil palm produces stable yield of more than 30 t ha-1 with increase in age of the palms, though there is reduction in number of bunches, improvement in average bunch weight contributes to the increase in yield per palm and per hectare.